Composite polyolefin elastomer as well as production method and application thereof

By adding vinyl bisharpened amide anti-adhesive rollers and composite antioxidants to the polyolefin elastomer, the problem of adhesive rollers during the photovoltaic film formation process is solved, efficient cast film processing is achieved, and the finished product is improved rate and productivity.

CN119286112AInactive Publication Date: 2025-01-10XINJIANG DUSHANZI PETROCHEMICAL CO LTD +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411846815.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyolefin elastomers are prone to sticking rollers during the photovoltaic adhesive film formation process, resulting in a reduced yield and low production efficiency. The existing solutions are complex and technically difficult.

Method used

Using vinyl bisharic amide as anti-adhesive rollers, the formulation design with polyolefin elastomer is combined with composite antioxidants to improve the adhesive roller problems of polymers during film formation. The cast film processing technology is used to prepare Broken film and wrinkle-free photovoltaic adhesive film.

Benefits of technology

It effectively avoids the adhesion phenomenon of polyolefin elastomer particles during film formation, improves the film formation rate and processing efficiency of the photovoltaic adhesive film, reduces film thickness unevenness and processing defects, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a composite polyolefin elastomer as well as a production method and application thereof, and belongs to the technical field of petrochemical engineering. The raw materials for preparing the composite polyolefin elastomer comprise a polyolefin elastomer, a composite antioxidant and an anti-sticking roller agent, the anti-sticking roller agent comprises vinyl bis-stearamide, and the mass ratio of the polyolefin elastomer to the anti-sticking roller agent is 1000: (0.1-8). The production method comprises the following steps: mixing the polyolefin elastomer, the composite antioxidant and the anti-sticking roller agent according to a formula to obtain a mixture; the mixture is subjected to mixing melting and extrusion granulation, and the composite polyolefin elastomer is obtained; wherein the outlet temperature of a melting pump for mixing and melting is 175-295 DEG C. According to the invention, vinyl bistearamide is adopted as an anti-sticking roller agent, so that the adhesion phenomenon between the composite polyolefin elastomer particles and a cold roller of a cast film machine during film forming is avoided, and the film forming rate of the composite polyolefin elastomer photovoltaic adhesive film is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petrochemical industry, and in particular relates to a composite polyolefin elastomer and a production method and application thereof. Background Art

[0002] Polyolefin elastomer (POE) is an elastomer polymerized by ethylene and α-olefin under the action of a homogeneous metal catalyst. It has a wide range of uses. It can be used as a rubber, a thermoplastic elastomer, and a plastic impact modifier and toughening agent. It has been well applied in the toughening modification of a variety of plastics and has posed a strong competition to traditional toughening agents.

[0003] POE was first synthesized by Dupont Dow Elastomers in the United States using the high-temperature solution Insite process and a constrained geometry metallocene catalyst (CGC), and was industrialized in 1993. Polyolefin elastomers on the market mainly include elastomers formed by random copolymerization of ethylene with 1-octene, 1-butene or 1-hexene.

[0004] Since the POE molecular chain has a high content of comonomers and low density, and the polymer chain is composed of a crystalline resin phase and an amorphous rubber phase, the material has both the high elasticity of rubber and the plasticity of thermoplastic resin, and is easy to process and shape. At the same time, the POE molecular chain is composed of non-polar saturated single bonds and has no polar groups, so it has excellent water vapor resistance, aging resistance, corrosion resistance and heat resistance, and can be widely used in medical equipment, wires and cables, automobile manufacturing, construction materials and toys.

[0005] At present, POE products are often used in the production of photovoltaic films, automotive material modification, foaming, and electrical material modification. In photovoltaic film applications, POE has excellent water vapor barrier properties, which can greatly improve the performance of potential induced degradation (PID) resistance and avoid the weaknesses of EVA films. However, POE materials also have their own shortcomings, mainly that bubbles are easily generated during use, the lamination yield of photovoltaic modules is low, and a large amount of functional additives need to be added to solve the problem of sticking to the roller. Due to the high content of comonomers and low density of POE products, their shear thinning effect is more obvious. The residual heat after processing will cause the film to not be fully crystallized, which is prone to sticking to the roller. POE particle sticking to the roller brings many production problems to photovoltaic film companies. The most notable is the film breakage phenomenon, which will greatly reduce the film production yield and seriously affect production efficiency.

[0006] During the film-forming process of polymers, the phenomenon of sticking to the roller is a common processing problem. At present, the following methods are usually used to solve the problem of sticking to the roller during the film-forming process of polymers: adding different types of comonomers during the polymerization stage; or forming the product into a multi-layer composite film; or adding conventional resin lubricants.

[0007] The Chinese patent document with publication number CN116285717A discloses a polyolefin photovoltaic adhesive film, which uses polyolefin elastomer POE, and a certain proportion of modified resin, silane oligomer and silane end-capping agent, additives and other components, so that each component cooperates with each other to obtain a polyolefin adhesive film with improved anti-skid and aging resistance. It does not slip when applied to the battery assembly end, and the film exhausts smoothly during lamination, is not easy to produce bubbles, and has a high peel strength retention rate with glass plates and battery cells under high temperature, high humidity and ultraviolet aging environments. The surface friction coefficient of the polyolefin photovoltaic adhesive film in this patent is ≥0.5. If the material friction coefficient is too large, it will easily stick to the roller during film processing, causing wrinkles, ripples and holes on the film surface.

[0008] The Chinese patent document with the publication number of patent CN104774361A discloses a polyethylene / polybutene thermoplastic elastomer alloy material, including polybutene with a mass fraction of 5 to 98.9, polyethylene with a mass fraction of 1 to 80, and ethylene-butene copolymer with a mass fraction of 0.1 to 20. The invention uses a polyethylene / polybutene thermoplastic elastomer alloy material synthesized by a multi-stage sequential polymerization method using a loaded titanium and / or vanadium catalyst, wherein after ethylene prepolymerization, a first stage of bulk polymerization generates active polyethylene particles that can continue to initiate butene-1 polymerization, and the polyethylene shell can prevent the adhesion of polymer particles during the polymerization of butene-1, and then further bulk polymerization of ethylene and butene-1 is carried out in sequence, and so on. Although this patent solves the problem of adhesion of polymer particles caused by low isotacticity during the polymerization of butene-1, the solution path relies on the polymerization process, the adjustment process is difficult, the technical difficulty is large, and the solution measures are complicated. Summary of the invention

[0009] The present invention provides a composite polyolefin elastomer and a production method and application thereof, adopting a formula design of a high temperature resistant lubricating additive, that is, adding a composite antioxidant and an anti-roller sticking agent to improve the roller sticking problem of the polymer in the film forming process.

[0010] In a first aspect, the present invention provides a composite polyolefin elastomer, and the raw materials for preparing the composite polyolefin elastomer include the following components: Polyolefin elastomer, composite antioxidant and anti-sticking roller agent, wherein: The anti-sticking roller agent includes vinyl bis-hard amide (abbreviated as EBS), and the mass ratio of polyolefin elastomer to the anti-sticking roller agent is 1000:0.1 to 8; The polyolefin elastomer has a number average molecular weight Mn of 12000 g / mol to 70000 g / mol, or a weight average molecular weight Mw of 40000 g / mol to 120000 g / mol, and a molecular weight distribution index of 1.2 to 4.1; The polyolefin elastomer is prepared by polymerization of ethylene and α-olefin under the action of a metallocene catalyst, wherein the α-olefin comprises at least one of butene, hexene and octene, and the molar ratio of the α-olefin to the ethylene is 0.1 to 0.5:1; The glass transition temperature of polyolefin elastomers is -45°C to -35°C.

[0011] As an optional embodiment, the density of the polyolefin elastomer is 0.855 g / cm 3 Up to 0.890g / cm 3 .

[0012] As an optional embodiment, the polyolefin elastomer has a melt index of 0.3 g / 10 min to 30 g / 10 min at 190° C. and a load of 2.16 kg.

[0013] As an optional embodiment, the composite antioxidant includes a primary antioxidant and an auxiliary antioxidant.

[0014] As an optional embodiment, the primary antioxidant is at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (also known as: antioxidant 1010) and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester (also known as: antioxidant 1076).

[0015] As an optional embodiment, the auxiliary antioxidant is at least one of tris(2,4-di-tert-butylphenyl)phosphite (also known as antioxidant 168) and bis(2,4-di-tert-butylphenyl)propionate] pentaerythritol diphosphite (also known as antioxidant 626).

[0016] As an optional embodiment, the mass ratio of the polyolefin elastomer to the primary antioxidant is 1000:0.1 to 4.

[0017] As an optional embodiment, the mass ratio of the polyolefin elastomer to the auxiliary antioxidant is 1000:0.1 to 3.5.

[0018] As an optional embodiment, the mass ratio of the primary antioxidant to the auxiliary antioxidant is (2 to 3): (0.8 to 5).

[0019] As an optional embodiment, the critical shear rate of the composite polyolefin elastomer at 80°C is 190 to 300 s -1, amplitude is 30 MPa to 50 MPa (tested by high pressure capillary rheometer).

[0020] As an optional embodiment, the difference in torque between 3 min and 30 min of the composite polyolefin elastomer at a shear temperature of 235° C. is less than 0.2 N (Haake torque rheometer test).

[0021] As an optional embodiment, when the composite polyolefin elastomer is subjected to cast film processing at a temperature of 85° C., the screw torque (or main motor torque) is 25 Nm to 60 Nm (tested by a cast film processing instrument).

[0022] In the present invention, during the cast film processing, the main motor drives the screw to rotate, so the torque of the screw can also represent the torque of the main motor.

[0023] In the present invention, the composite polyolefin elastomer is used to prepare a 20 μm thick cast film using a 300 mm width cast film machine, the stretching speed is 15 m / min, and there is no film breakage or wrinkling within 2 hours.

[0024] In a second aspect, the present invention provides a method for producing the composite polyolefin elastomer, the production method comprising the following steps: The polyolefin elastomer, the composite antioxidant and the anti-sticking roller agent are mixed according to a formula to obtain a mixture; The mixture is kneaded, melted and extruded into granules to obtain a composite polyolefin elastomer.

[0025] In the present invention, based on the same inventive concept, the components and contents contained in the above-mentioned composite polyolefin elastomer are still applicable in its production method and will not be repeatedly introduced here.

[0026] As an optional implementation, the polyolefin elastomer is a powder.

[0027] As an optional embodiment, the melt pump outlet temperature of the mixed melting is 175°C to 295°C.

[0028] As an optional implementation manner, the inlet pressure of the melt pump for mixing and melting is 1 MPa to 4 MPa.

[0029] As an optional embodiment, the pressure difference before and after the molten mixing screen is 1.5 MPa to 8.4 MPa.

[0030] As an optional embodiment, the water temperature of the granules during extrusion granulation is 10°C to 60°C.

[0031] In a third aspect, the present invention provides an application of a composite polyolefin elastomer in the field of photovoltaic films. The composite polyolefin elastomer is prepared by using any of the above composite polyolefin elastomers, or by any of the above production methods of the composite polyolefin elastomers.

[0032] In the present invention, the above technical features can be freely combined to form a new technical solution without conflicting with each other.

[0033] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects: (1) The present invention uses vinyl bis-hard amide as an anti-sticking roller agent to prevent the composite polyolefin elastomer particles from sticking to the cold roller of the cast film machine during film formation. Even at a high stretching speed, the film can be formed smoothly, thereby greatly improving the film formation rate of the composite polyolefin elastomer photovoltaic film; (2) The present invention uses vinyl bis-hard amide as an anti-stick roller agent, which can solve the problem of poor material feeding of photovoltaic film due to the lack of lubrication of POE particles, and avoid problems such as film thickness exceeding the specified range and low processing efficiency. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0035] In order to facilitate transportation, storage and subsequent processing, metallocene polyethylene powder is usually made into pellets in an extrusion granulator through mixing, extrusion, pelletizing and other processes. For conventional polyethylene, its density (0.890 g / cm 3 Up to 0.960g / cm 3 ) is high, and the viscosity of the molten material is low. Therefore, when extruding and pelletizing, no anti-sticking agent is needed. The material has good rigidity, and the film surface will not stick to the roller during film forming. The density of polyolefin elastomer (0.855g / cm 3 Up to 0.890g / cm 3 ) is low, the melting point (35℃ to 70℃) is low, and it shows strong flexibility when processed into film. During the stretching process, the film surface is extremely rough in the microscopic state. In order to ensure the processing efficiency, it needs to be stretched quickly, which makes it easy for the film surface to stick to the cold roller, resulting in defects such as film breakage, wrinkles, and moiré, which reduces the overall processing yield.

[0036] To this end, the inventors intend to provide a composite polyolefin elastomer and a production method thereof. First, EBS is introduced as an anti-sticking agent, and then the problem of POE film easily sticking to the roller is solved through an extrusion granulation production method, so that the POE particles meet the processing requirements of downstream customers.

[0037] Some embodiments of the present invention provide a composite polyolefin elastomer, and the raw materials for preparing the composite polyolefin elastomer include the following components: Polyolefin elastomer, composite antioxidant and anti-sticking roller agent, wherein: Polyolefin elastomers are produced by polymerization of ethylene and α-olefins with metallocene catalysts; Composite antioxidants include primary antioxidants and auxiliary antioxidants; The anti-sticking roller agent includes vinyl bis-hard amide EBS, and the mass ratio of the polyolefin elastomer to the anti-sticking roller agent is 1000:0.1 to 8 (for example, 1000:0.5, 1000:1, 1000:2, 1000:3, 1000:4, 1000:5, 1000:6 or 1000:7).

[0038] In some embodiments, the α-olefin includes at least one of butene, hexene, and octene, and the molar ratio of the α-olefin to ethylene is 0.1 to 0.5:1 (eg, 0.2:1, 0.3:1, or 0.4:1).

[0039] In some embodiments, the polyolefin elastomer has a density of 0.855 g / cm 3 Up to 0.890 g / cm 3 ; The weight average molecular weight Mw is 40,000 g / mol to 120,000 g / mol, or the number average molecular weight Mn is 12,000 g / mol to 70,000 g / mol, and the molecular weight distribution index is 1.2 to 4.1; the melt index of the polyolefin elastomer at 190°C and 2.16 kg load is 0.3 g / 10min to 30 g / 10 min.

[0040] In the present invention, the Shore hardness of the polyolefin elastomer raw material for preparing the composite polyolefin elastomer is 80 to 85, the glass transition temperature is -45°C to -35°C, and the light transmittance is 86% to 90%, which is lower than the Shore hardness (90 to 95) of the general ethylene plastomer film material, the glass transition temperature (-120°C to -100°C) is higher, and the light transmittance (general polyethylene is 82% to 85%) is better. Therefore, compared with the general ethylene plastomer film material, the higher glass transition temperature makes it easier to stick to the roller during the film processing.

[0041] Therefore, the present invention adopts a composite antioxidant and an anti-sticking roller agent additive formula to reduce the sticking roller problem of polyolefin elastomers during the film forming process. Among them, EBS is used as the anti-sticking roller agent of the present invention. If the amount is too little, it will not have the anti-sticking roller effect; if the amount is too much, since EBS is a small molecule, it will cause the following problems: ① small molecule precipitates accumulate in the die head, and the die head needs to be shut down and cleaned regularly, affecting the processing efficiency; ② the smoke in the processing plant is very thick, polluting the environment. Therefore, it is necessary to reasonably design the amount of the anti-sticking roller agent to ensure processing efficiency and avoid environmental pollution while solving the sticking roller problem.

[0042] In some embodiments, the primary antioxidant is at least one of antioxidant 1010 and antioxidant 1076; the auxiliary antioxidant is at least one of antioxidant 168 and antioxidant 626; the mass ratio of polyolefin elastomer to the primary antioxidant is 1000:0.1 to 4, and the mass ratio of polyolefin elastomer to the auxiliary antioxidant is 1000:0.1 to 3.5.

[0043] In some embodiments, the mass ratio of the primary antioxidant to the secondary antioxidant is (2 to 3):(0.8 to 5) (eg, 2.5:(0.8 to 5), 2:(0.8 to 5) or 3:(0.8 to 5)).

[0044] In some embodiments, the critical shear rate of the composite polyolefin elastomer at 80° C. (measured using a high pressure capillary rheometer) is 190 to 300 s -1 , the amplitude is 30 MPa to 50 MPa; the torque difference between 3min and 30min of the composite polyolefin elastomer is less than 0.2 N at a shear temperature of 235℃ (Haake torque rheometer test); when the composite polyolefin elastomer is processed into cast film at a temperature of 85℃, the screw torque (or main motor torque) is between 25 Nm and 60 Nm (tested by cast film processing instrument).

[0045] In the present invention, the composite polyolefin elastomer is prepared into a 20 μm thick cast film using a 300 mm width cast film machine, the stretching speed is 15 m / min, and there is no film breakage or wrinkling within 2 hours.

[0046] Some embodiments of the present invention also provide a method for producing any of the above composite polyolefin elastomers, comprising the following steps: The polyolefin elastomer, the composite antioxidant and the anti-sticking roller agent are mixed according to a formula to obtain a mixture; The mixture is kneaded, melted and extruded into granules to obtain a composite polyolefin elastomer.

[0047] In the present invention, based on the same inventive concept, the components and contents of the above-mentioned anti-particle adhesion polyolefin elastomer are still applicable in its production method and will not be repeatedly introduced here.

[0048] In some embodiments, the polyolefin elastomer is in the form of a powder.

[0049] In some embodiments, the melt pump outlet temperature of the mixed melt is 175°C to 295°C (e.g., 180°C, 190°C, 200°C, 220°C, 250°C, 270°C, 280°C, or 285°C), the melt pump inlet pressure is 1 MPa to 4 MPa (e.g., 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, or 3.5 MPa), and the pressure difference before and after the mixed melt screen is 1.5 MPa to 8.4 MPa (e.g., 2 MPa, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, or 8 MPa).

[0050] In some embodiments, the granulation water temperature of the extrusion granulation is 10°C to 60°C (eg, 20°C, 30°C, 40°C, or 50°C).

[0051] The present invention adopts vinyl bis-hard amide as an anti-sticking roller agent. Vinyl bis-hard amide is a relatively small molecule and has good compatibility with polyolefin elastomers. It not only has a good external lubrication effect, but also has a good internal lubrication effect, and can form a durable lubrication effect on polyolefin elastomer particles. In addition, the anti-sticking roller agent can be precipitated onto the particle surface during the granulation shearing process, thereby preventing the composite polyolefin elastomer particles from sticking to the cold roller of the cast film machine during film formation, thereby greatly improving the film formation rate of the composite polyolefin elastomer photovoltaic film.

[0052] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0053] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0054] Specifically, the present invention uses a high-pressure capillary rheometer to test the critical shear rate of the polyolefin elastomer at 80° C., uses a Haake torque rheometer to test the torque of the polyolefin elastomer, and uses a cast film processor to test the torque of the polyolefin elastomer.

[0055] Example 1 A composite polyolefin elastomer (composite POE for short) is prepared using the following raw materials: Polyolefin elastomer; powder (hereinafter referred to as: POE powder); the density of the POE powder is 0.886 g / cm 3 , the number average molecular weight Mn is 51000 g / mol, the weight average molecular weight Mw is 110000 g / mol, the molecular weight distribution index is 2.2, and the melt index at 190°C and 2.16 kg load is 0.8 g / 10 min; when producing the POE powder, the molar ratio of α-olefin to ethylene is 0.11:1; Anti-stick roller agent; EBS, the addition amount is 1000 mg / kg POE powder (i.e., 1000 mg EBS is added per kg POE powder); wherein, Composite antioxidant; the composite antioxidant comprises a main antioxidant 1010 and an auxiliary antioxidant 168, wherein the addition amount of the main antioxidant 1010 is 400 mg / kg POE powder, and the addition amount of the auxiliary antioxidant 168 is 200 mg / kg POE powder.

[0056] The production method of the composite polyolefin elastomer comprises the following steps: POE powder, anti-stick roller agent and composite antioxidant are added into the barrel of the extruder according to the above formula for mixing, melting and extrusion granulation to obtain a composite polyolefin elastomer, wherein the outlet temperature of the melt pump of the extruder mixing and melting is 195°C, the inlet pressure of the melt pump of the extruder mixing and melting is 3.5 MPa, the pressure difference before and after the screen of the molten material is 1.8 MPa, and the temperature of the granule water (also called: pelletizing water) of the extrusion granulation is 12°C.

[0057] The composite polyolefin elastomer prepared in this embodiment has a critical shear rate of 267 s at 80°C for its high pressure capillary rheology melt. -1 , amplitude is 45 MPa; the torque difference between 3 min and 30 min of the composite polyolefin elastomer at a shear temperature of 235°C was measured by a Haake torque rheometer, which was 0.17 N; the main engine torque of the composite polyolefin elastomer was 42 Nm at a processing temperature of 85°C measured by a cast film processor.

[0058] The composite polyolefin elastomer prepared in this embodiment was prepared into a 20 μm thick cast film using a 300 mm width cast film machine, wherein the stretching speed was 15 m / min; the cast film had no film breakage or wrinkles within 2 hours, and the film surface thickness exceeded 20±4 μm (i.e., 16 μm to 24 μm) at 0 locations.

[0059] It can be seen that the composite polyolefin elastomer prepared in this embodiment has the property of anti-sticking to rollers.

[0060] Example 2 A composite polyolefin elastomer is prepared using the following raw materials: Polyolefin elastomer; powder (hereinafter referred to as: POE powder); the density of the POE powder is 0.875 g / cm 3 , the number average molecular weight Mn is 42000 g / mol, the weight average molecular weight Mw is 95000 g / mol, the molecular weight distribution index is 2.3, and the melt index at 190°C and 2.16 kg load is 5 g / 10 min; when producing the POE powder, the molar ratio of α-olefin to ethylene is 0.24:1; Anti-stick roller agent: EBS, the addition amount is 3000 mg / kg POE powder; Composite antioxidant; the composite antioxidant comprises a main antioxidant 1076 and an auxiliary antioxidant 626, wherein the addition amount of the main antioxidant 1076 is 2000 mg / kg POE powder, and the addition amount of the auxiliary antioxidant 626 is 1500 mg / kg POE powder.

[0061] The production method of the composite polyolefin elastomer comprises the following steps: POE powder, anti-stick roller agent and composite antioxidant are added into the barrel of the extruder according to the above formula for mixing, melting and extrusion granulation to obtain a composite polyolefin elastomer, wherein the outlet temperature of the extruder mixing, melting and melting pump is 215°C, the inlet pressure of the extruder mixing, melting and melting pump is 2.2 MPa, the pressure difference before and after the screen of the molten material is 3 MPa, and the water temperature of the extruded granulated particles is 30°C.

[0062] The composite polyolefin elastomer prepared in this embodiment has a critical shear rate of 256 s at 80°C for its high pressure capillary rheology melt. -1 , amplitude is 43 MPa; the torque difference between 3 min and 30 min of the composite polyolefin elastomer at a shear temperature of 235°C was measured by a Haake torque rheometer, which was 0.13 N; the main engine torque of the composite polyolefin elastomer was 33 Nm at a processing temperature of 85°C measured by a cast film processor.

[0063] The composite polyolefin elastomer prepared in this embodiment was prepared into a 20 μm thick cast film using a 300 mm width cast film machine, wherein the stretching speed was 15 m / min; the cast film had no film breakage or wrinkles within 2 hours, and the film surface thickness exceeded 20±4 μm (i.e., 16 μm to 24 μm) at 0 locations.

[0064] It can be seen that the composite polyolefin elastomer prepared in this embodiment has the property of anti-sticking to rollers.

[0065] Example 3 A composite polyolefin elastomer is prepared using the following raw materials: Polyolefin elastomer; powder (hereinafter referred to as: POE powder); the density of the POE powder is 0.860 g / cm 3 , the number average molecular weight Mn is 27000 g / mol, the weight average molecular weight Mw is 60000 g / mol, the molecular weight distribution index is 2.2, and the melt index at 190°C and 2.16 kg load is 14 g / 10 min; when producing the POE powder, the molar ratio of α-olefin to ethylene is 0.35:1; Anti-stick roller agent; EBS, the addition amount is 3500 mg / kg POE powder; Composite antioxidant; the composite antioxidant comprises a main antioxidant 1076 and an auxiliary antioxidant 168, wherein the addition amount of the main antioxidant 1076 is 3000 mg / kg POE powder, and the addition amount of the auxiliary antioxidant 168 is 3500 mg / kg POE powder.

[0066] The production method of the composite polyolefin elastomer comprises the following steps: POE powder, anti-stick roller agent and composite antioxidant are added into the barrel of the extruder according to the above formula for mixing, melting and extrusion granulation to obtain a composite polyolefin elastomer, wherein the outlet temperature of the extruder mixing, melting and melting pump is 245°C, the inlet pressure of the extruder mixing, melting and melting pump is 1.1 MPa, the pressure difference before and after the screen of the molten material is 4.7 MPa, and the water temperature of the extruded granulated particles is 55°C.

[0067] The composite polyolefin elastomer prepared in this embodiment has a critical shear rate of 205 s at 80°C for its high pressure capillary rheology melt. -1 , amplitude is 34 MPa; the torque difference between 3 min and 30 min of the composite polyolefin elastomer at a shear temperature of 235°C was measured by a Haake torque rheometer, which was 0.08 N; the main engine torque of the composite polyolefin elastomer was 30 Nm at a processing temperature of 85°C measured by a cast film processor.

[0068] The composite polyolefin elastomer prepared in this embodiment was prepared into a 20 μm thick cast film using a 300 mm width cast film machine, wherein the stretching speed was 15 m / min; the cast film had no film breakage or wrinkles within 2 hours, and the film surface thickness exceeded 20±4 μm (i.e., 16 μm to 24 μm) at 0 locations.

[0069] It can be seen that the composite polyolefin elastomer prepared in this embodiment has the property of anti-sticking to rollers.

[0070] Comparative Example 1 A composite polyolefin elastomer is prepared using the following raw materials: Polyolefin elastomer; powder (hereinafter referred to as: POE powder); the density of the POE powder is 0.886 g / cm 3 , the number average molecular weight Mn is 51000 g / mol, the weight average molecular weight Mw is 110000 g / mol, the molecular weight distribution index is 2.2, and the melt index at 190°C and 2.16 kg load is 0.8 g / 10 min; when producing the POE powder, the molar ratio of α-olefin to ethylene is 0.11:1; Composite antioxidant; the composite antioxidant comprises a main antioxidant 1010 and an auxiliary antioxidant 168, wherein the addition amount of the main antioxidant 1010 is 400 mg / kg POE powder, and the addition amount of the auxiliary antioxidant 168 is 200 mg / kg POE powder.

[0071] The production method of the composite polyolefin elastomer comprises the following steps: POE powder, anti-stick roller agent and composite antioxidant are added into the barrel of the extruder according to the above formula for mixing, melting and extrusion granulation to obtain a composite polyolefin elastomer, wherein the outlet temperature of the extruder mixing, melting and melting pump is 195°C, the inlet pressure of the extruder mixing, melting and melting pump is 3.6 MPa, the pressure difference before and after the screen of the molten material is 1.9 MPa, and the water temperature of the extruded granulated particles is 12°C.

[0072] The composite polyolefin elastomer prepared in this comparative example has a critical shear rate of 265 s at 80°C for its high pressure capillary rheology melt. -1 , amplitude is 46 MPa; the torque difference between 3 min and 30 min of the composite polyolefin elastomer at a shear temperature of 235°C was measured by a Haake torque rheometer, which was 0.19 N; the main engine torque of the composite polyolefin elastomer was 44 Nm at a processing temperature of 85°C measured by a cast film processor.

[0073] The composite polyolefin elastomer prepared in this comparative example was prepared into a 20 μm thick cast film using a 300 mm width cast film machine, wherein the stretching speed was 15 m / min; the cast film formed 12 film holes and 22 wrinkle areas within 2 hours, and the film surface thickness exceeded 20±4 μm (i.e., 16 μm to 24 μm) at 0 locations.

[0074] It can be seen that the composite polyolefin elastomer prepared in this comparative example has poorer anti-roller sticking performance than the composite polyolefin elastomer in Example 1.

[0075] Comparative Example 2 A composite polyolefin elastomer is prepared using the following raw materials: Polyolefin elastomer; powder (hereinafter referred to as: POE powder); the density of the POE powder is 0.875 g / cm 3 , the number average molecular weight Mn is 42000 g / mol, the weight average molecular weight Mw is 95000 g / mol, the molecular weight distribution index is 2.3, and the melt index at 190°C and 2.16 kg load is 5 g / 10 min; when producing the POE powder, the molar ratio of α-olefin to ethylene is 0.24:1; Anti-stick roller agent: EBS, the addition amount is 3000 mg / kg POE powder; Composite antioxidant; the composite antioxidant comprises a main antioxidant 1076 and an auxiliary antioxidant 626, wherein the addition amount of the main antioxidant 1076 is 2000 mg / kg POE powder, and the addition amount of the auxiliary antioxidant 626 is 1500 mg / kg POE powder.

[0076] The production method of the composite polyolefin elastomer comprises the following steps: POE powder, anti-stick roller agent and composite antioxidant are added into the barrel of the extruder according to the above formula for mixing, melting and extrusion granulation to obtain a composite polyolefin elastomer, wherein the outlet temperature of the melt pump of the extruder mixing and melting is 265°C, the inlet pressure of the melt pump of the extruder mixing and melting is 0.6 MPa, the pressure difference before and after the screen of the molten material is 1 MPa, and the water temperature of the particles of the extrusion granulation is 65°C.

[0077] The composite polyolefin elastomer prepared in this comparative example has a critical shear rate of 248 s at 80°C for its high pressure capillary rheology melt. -1 , amplitude is 39 MPa; the torque difference between 3 min and 30 min of the composite polyolefin elastomer at a shear temperature of 235°C was measured by a Haake torque rheometer, which was 0.16 N; the main engine torque of the composite polyolefin elastomer was 33 Nm at a processing temperature of 85°C measured by a cast film processor.

[0078] The composite polyolefin elastomer prepared in this comparative example was prepared into a 20 μm thick cast film using a 300 mm width cast film machine, wherein the stretching speed was 15 m / min; the cast film had no film breakage or wrinkles within 2 hours, but due to the large number of large particles and tailing particles and uneven feeding, the film surface thickness exceeded 20±4 μm (i.e., 16 μm to 24 μm) in 78 places.

[0079] It can be seen that the use of a higher granulation temperature in this comparative example leads to an increase in the number of large and small particles in the product, and the material feeding is not smooth during the film forming process, resulting in uneven thickness of the prepared film.

[0080] Comparative Example 3 A composite polyethylene resin is prepared using the following raw materials: Polyethylene resin powder; the polyethylene resin powder is prepared by polymerization of ethylene and α-olefin under the action of a metallocene catalyst, wherein the molar ratio of α-olefin to ethylene is 0.009:1; the density of the polyethylene resin powder is 0.919 g / cm 3 , the number average molecular weight Mn is 12700 g / mol, the weight average molecular weight Mw is 53000 g / mol, the molecular weight distribution index is 1.8, and the melt index at 190°C and 2.16 kg load is 0.92 g / 10 min; when producing the polyethylene resin powder, the molar ratio of α-olefin to ethylene is 0.35:1; Anti-stick roller agent; EBS, the addition amount is 1000 mg / kg polyethylene resin powder (that is, 1000 mg EBS is added per kg polyethylene resin powder); wherein, Composite antioxidant; the composite antioxidant comprises a primary antioxidant 1010 and an auxiliary antioxidant 168, wherein the primary antioxidant 1010 is added in an amount of 400 mg / kg polyethylene resin powder, and the auxiliary antioxidant 168 is added in an amount of 200 mg / kg polyethylene resin powder.

[0081] The production method of the composite polyethylene resin comprises the following steps: Polyethylene resin powder, anti-sticking roller agent and composite antioxidant are added into the barrel of the extruder according to the above formula for mixing, melting and extrusion granulation to obtain composite polyethylene resin, wherein the outlet temperature of the melt pump of the extruder mixing and melting is 195°C, the inlet pressure of the melt pump of the extruder mixing and melting is 5.7 MPa, the pressure difference before and after the screen of the molten material is 1.9 MPa, and the temperature of the granule water (also called: pelletizing water) of the extrusion granulation is 12°C.

[0082] The composite polyethylene resin prepared in this comparative example has a critical shear rate of 293 s at 80°C for its high pressure capillary rheology melt. -1 , amplitude is 50 MPa; using the Haake torque rheometer to measure at a shear temperature of 235°C, the torque difference between 3 min and 30 min is 0.16 N; the cast film processor measures the main engine torque at a processing temperature of 85°C at 57 Nm.

[0083] The composite polyethylene resin prepared in this comparative example was subjected to a casting film forming experiment using a 300 mm width casting film machine at a stretching speed of 15 m / min. The results showed that no film could be formed.

[0084] Comparative Example 4 This comparative example provides a composite polyolefin elastomer and a production method thereof, which is different from Example 1 in that the addition amount of the anti-sticking roller agent EBS is 8500 mg / kg POE powder.

[0085] The composite polyolefin elastomer prepared in this comparative example has a critical shear rate of 259 s at 80°C for its high pressure capillary rheology melt. -1 , amplitude is 44 MPa; the torque difference between 3 min and 30 min of the composite polyolefin elastomer at a shear temperature of 235°C was measured by a Haake torque rheometer, which was 0.18 N; the main engine torque of the composite polyolefin elastomer was 39 Nm at a processing temperature of 85°C measured by a cast film processor.

[0086] In addition, since too much EBS was added during the production of the composite polyolefin elastomer, the smoke in the processing workshop was heavier and the number of particles in the air increased compared to Example 1, and the number of particles larger than 0.5 μm in the air of the production workshop was about 5.12 million / cubic feet. In Example 1, during the production period, the number of particles larger than 0.5 μm in the air of the production workshop was only about 1.6 million / cubic feet.

[0087] The cast films made of the composite polyolefin elastomer or composite polyethylene resin prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested, and the results are shown in Table 1.

[0088] Table 1: .

[0089] It can be seen from Table 1 that the film made of the composite polyolefin elastomer prepared by the method provided in Examples 1 to 3 of the present invention has no film breakage, no wrinkles, and no excessive film thickness caused by bridging and uneven feeding. On the contrary, the composite polyolefin elastomer prepared by the method provided in Comparative Examples 1 to 2 has many film holes and wrinkles during film formation, and the film surface is easily excessively thick.

Claims

1. A composite polyolefin elastomer, characterized in that: The raw materials for preparing composite polyolefin elastomers include the following components: Polyolefin elastomer, composite antioxidant and anti-sticking roller agent, wherein: The anti-sticking roller agent includes vinyl bis-hard amide, and the mass ratio of the polyolefin elastomer to the anti-sticking roller agent is 1000:0.1 to 8; The polyolefin elastomer has a number average molecular weight Mn of 12000 g / mol to 70000 g / mol, or a weight average molecular weight Mw of 40000 g / mol to 120000 g / mol, and a molecular weight distribution index of 1.2 to 4.1; The polyolefin elastomer is prepared by polymerization of ethylene and α-olefin under the action of a metallocene catalyst, wherein the α-olefin comprises at least one of butene, hexene and octene, and the molar ratio of the α-olefin to the ethylene is 0.1 to 0.5:1; The glass transition temperature of polyolefin elastomers is -45°C to -35°C.

2. The composite polyolefin elastomer according to claim 1, characterized in that: The density of polyolefin elastomer is 0.855g / cm 3 Up to 0.890g / cm 3 .

3. The composite polyolefin elastomer according to claim 1 or 2, characterized in that: The polyolefin elastomer has a melt index of 0.3 g / 10 min to 30 g / 10 min at 190° C. and a load of 2.16 kg.

4. The composite polyolefin elastomer according to claim 3, characterized in that: The composite antioxidant includes a primary antioxidant and an auxiliary antioxidant; wherein, The primary antioxidant is at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; The auxiliary antioxidant is at least one of tris(2,4-di-tert-butylphenyl)phosphite and bis(2,4-di-tert-butylphenyl)propionate]pentaerythritol diphosphite.

5. The composite polyolefin elastomer according to claim 4, characterized in that: The mass ratio of the polyolefin elastomer to the primary antioxidant is 1000:0.1 to 4; The mass ratio of the polyolefin elastomer to the auxiliary antioxidant is 1000:0.1 to 3.

5.

6. The composite polyolefin elastomer according to claim 5, characterized in that: The mass ratio of the primary antioxidant to the auxiliary antioxidant is 2 to 3:0.8 to 5.

7. The composite polyolefin elastomer according to claim 1 or 2 or 4 or 5 or 6, characterized in that: The critical shear rate of composite polyolefin elastomer at 80°C is 190s -1 Up to 300 s -1 , with an amplitude of 30 MPa to 50 MPa; or / and, The difference between the torque of the composite polyolefin elastomer at a shear temperature of 235°C for 3 min and 30 min is less than 0.2 N; or / and, When composite polyolefin elastomer is processed into cast film at 85°C, the screw torque is between 25 Nm and 60 Nm.

8. A method for producing a composite polyolefin elastomer according to any one of claims 1 to 7, characterized in that: The production method comprises the following steps: The polyolefin elastomer, the composite antioxidant and the anti-sticking roller agent are mixed according to a formula to obtain a mixture; The mixture is kneaded, melted and extruded into granules to obtain a composite polyolefin elastomer.

9. The method for producing a composite polyolefin elastomer according to claim 8, characterized in that: The melt pump outlet temperature of the mixed melt is 175°C to 295°C.

10. The method for producing a composite polyolefin elastomer according to claim 9, characterized in that: The melt pump inlet pressure for mixing and melting is 1 MPa to 4 MPa.

11. The method for producing a composite polyolefin elastomer according to claim 10, characterized in that: The pressure difference before and after the sieve for mixing and melting is 1.5 MPa to 8.4 MPa.

12. The method for producing a composite polyolefin elastomer according to claim 9, 10 or 11, characterized in that: The granule water temperature for extrusion granulation is 10°C to 60°C.

13. Application of a composite polyolefin elastomer in the field of photovoltaic films, characterized in that: The composite polyolefin elastomer is prepared by the composite polyolefin elastomer described in any one of claims 1 to 7, or by the production method of the composite polyolefin elastomer described in any one of claims 8 to 12.

Citation Information

Patent Citations

  • Polyethylene / polybutene thermoplastic elastomer alloy material and preparation method thereof

    CN104774361A

  • Cross-linking low-smoke halogen-free and flame-retardant POE and preparation method thereof

    CN103073781A

  • Flexible polyolefin thermoplastic elastic material

    CN104725696A

  • POE talcum powder master batch

    CN106987048A

  • Ultraviolet intercepting thermoplastic polyolefin elastomer coating and application thereof

    CN109135590A